3(x + 4) = 27
First, since our variable is already on one side by itself, we can start out by dividing each side by 3.
[tex]x + 4 = \frac{27}{3} [/tex]
Second, we need to simplify our fraction we just got. To do so, think of it as this way: what times 3 equals 27? Or, (3 × x = 27). Either way, the answer is 9.
[tex]x + 4 = 9[/tex]
Third, we can remove (subtract) 4 from each side of the problem. This will give us the answer after we subtract it.
[tex]x = 9 - 4[/tex]
Fourth, our last step is to subtract 9 - 4 to get our answer. (9 - 4 = 5), meaning 5 is our answer.
Answer: [tex]\fbox {x = 5}[/tex]